Barriers to Mental Health Treatment Utilization in Wards 7 and 8 in Washington, DC: A Qualitative Pilot Study - Ollie Ganz; Laurel E. Curry; Laurel E. Curry; Paulette Jones; Katherine H. Mead; Monique M. Turner (Mary Ann Liebert, 2018)
Purpose: There is a paucity of data on barriers to mental health treatment utilization among residents of Wards 7 and 8 in Washington, DC, despite exposure to many environmental factors that are associated with poor mental health outcomes and the high prevalence of mental health problems among residents. The objective of this study was to examine barriers to mental healthcare utilization among residents of Wards 7 and 8. Methods: This study included semi-structured, in-depth interviews with five key informants who lived or spent significant time in Wards 7 or 8 in Washington, DC, which are the wards served by Paving the Way MSI, a behavioral health clinic that served as a partner organization in the study. Results: Barriers to mental health treatment utilization existed at a variety of social-ecological levels, including the individual/interpersonal level, the provider/mental health system level, the community level, and the societal level. Major barriers included fear and trust/distrust in the medical system, lack of social support, the model of mental healthcare, lack of patient-centered care, limited access to mental health services, stigma of mental illness and mental health treatment, and poverty. Conclusion: This study highlights the need to address barriers to mental health treatment utilization at multiple social-ecological levels. Future studies should examine perspectives from residents with mental health problems in these wards to gain a more thorough understanding of the barriers to treatment. Funding is needed to support efforts to increase mental health treatment utilization among residents of Wards 7 and 8.